Academic Health System in West Java in Strengthening Primary Health Care - Yoni Fuadah Syukriani (Universitas Andalas, 2020)
Academic Health System (AHS) has been developed in many countries to strengthen the relationship between medical education and health professions with the health care system, which is essential to improve health outcome. Indonesia has chosen to establish AHS in several provinces, each with the autonomy to develop the system in accord with regional needs. Health cluster faculties in Universitas Padjadjaran, with its two main teaching hospitals, the West Java provincial government strived to develop AHS to overcome health services problem and medical education in the province that has enormous geographical and demographic challenges. The strategy used focuses on two things: distributed medical education (DME) and the development of a more effective referral system. The goals are dividing the province into seven regionals, upscaling one local hospital in each to become a regional referral hospital, expanding learning opportunities for medical students, and endorsing research to strengthen the primary healthcare services. Activities were carried out through the distribution of medical students and residents to local hospitals and primary healthcare facilities along with the education of local medical professionals as supervisors. Grants were provided for research that focus on quality primary healthcare, construction of data portal for patient management referral systems, telemedicine, and tele-education. The challenges faced are mainly related to the different mindset between institutions that have different work cultures and the wide variance of situations between regions. It is therefore recommended to build a more straightforward AHS system with addition of sub-networks, besides continue to maintain close communication and policy development.